Subaortic and midventricular obstructive hypertrophic cardiomyopathy with extreme segmental hypertrophy - Karoulas Takis (Cardiovascular Ultrasound, 2007)
Abstract Background Subaortic and midventricular hypertrophic cardiomyopathy in a patient with extreme segmental hypertrophy exceeding the usual maximum wall thickness reported in the literature is a rare phenomenon. Case Presentation A 19-year-old man with recently diagnosed hypertrophic cardiomyopathy (HCM) was referred for sudden death risk assessment. The patient had mild exertional dyspnea (New York Heart Association functional class II), but without syncope or chest pain. There was no family history of HCM or sudden death. A two dimensional echocardiogram revealed an asymmetric type of LV hypertrophy; anterior ventricular septum = 49 mm; posterior ventricular septum = 20 mm; anterolateral free wall = 12 mm; and posterior free wall = 6 mm. The patient had 2 types of obstruction; a LV outflow obstruction due to systolic anterior motion of both mitral leaflets (Doppler-estimated 38 mm Hg gradient at rest); and a midventricular obstruction (Doppler-estimated 43 mm Hg gradient), but without apical aneurysm or dyskinesia. The patient had a normal blood pressure response on exercise test and no episodes of non-sustained ventricular tachycardia in 24-h ECG recording. Cardiac MRI showed a gross late enhancement at the hypertrophied septum. Based on the extreme degree of LV hypertrophy and the myocardial hyperenhancement, an implantation of a cardioverter-defibrillator was recommended prophylactically for primary prevention of sudden death. Conclusion Midventricular HCM is an infrequent phenotype, but may be associated with an apical aneurysm and progression to systolic dysfunction (end-stage HCM).